High temperature corrosion behaviour of steel with a Carbonate deposit at 1123K - Habsah, Md Ishak; Mohammed Misbahul, Amin; Nazree, Derman; Khairul Rafezi, Ahmad (School of Materials Engineering, 2009)
The high temperature corrosion behavior of A1S1 304 austenitic stainless steel and S45C carbon steel were studied in presence with CaCO3 salt at 1123K for 24,48,72, 96 and 120 hour. The studies were carried out to determine the mass change vs times, the morphological structures of deposits on the surface of alloy scales were investigated by scanning electron microscopy (SEM). The results indicated that the initial CaCO3 coating accelerated oxidation, resulting in the formation of a scales. The mass of metal was related to the consumption of chromium, nickel and iron in the alloy substrate. The characterization of scales were determined by using the EDAX.